Perfectly reliable and secure message transmission tolerating mobile adversary. (26th February 2009) - Patra, Arpita; Choudhary, Ashish; Rangan, C. Pandu; Srinathan, Kannan; , Prasad Raghavendra
We study the problem of perfectly reliable message transmission (PRMT) and perfectly secure message transmission (PSMT) in an undirected synchronous network tolerating an all powerful threshold mobile Byzantine adversary. Specifically, we show that the mobility of the threshold adversary does not affect the possibility and optimality of PRMT and PSMT protocols. We also characterise PSMT in directed networks tolerating mobile adversary. All existing PRMT and PSMT protocols abstract the paths between the sender and the receiver as wires, neglecting the intermediate nodes in the paths, thus causing significant over estimation in the communication and round complexity of protocols. Here, we consider the underlying paths as a whole instead of abstracting them as wires and derive a tight bound on the number of rounds required to achieve reliable communication tolerating a threshold mobile adversary with arbitrary roaming speed. Finally, we briefly study PRMT and PSMT protocols in the presence of non-threshold mobile Byzantine adversary. Even though the characterisation for PRMT/PSMT is shown to be same against both threshold static and threshold mobile adversary (in this article), we show that the characterisation for PRMT/PSMT against non-threshold static and non-threshold mobile adversary are not same.